EFFECT OF L-TRYPTOPHAN EFFECT OF L-TRYPTOPHAN ON THE MORPHO-FUNCTIONAL CHANGES OF WHITE ADIPOSE TISSUE AN INDUCED VISCERAL OBESITY RAT MODEL - Yanko, Roman (Polish Journal of Natural Sciences, 2023)
Visceral obesity (VO) is a widespread issue that contributes to the development of various diseases. Consequently, there is a need to identify effective methods for preventing VO. One of the ways to prevent VO can be the use of the amino acid tryptophan. This study aimed to investigate the impact of L-tryptophan on morpho-functional changes in white adipose tissue (WAT) in rats with VO and assess its potential for disease prevention. Male Wistar rats were involved in the study. Control animals (Group I) followed a standard diet, while Group II rats were fed a high-fat and high-carbohydrate diet for 12 weeks. Group III animals received a high-calorie diet supplemented with L-tryptophan (80 mg/kg). Blood and tissue samples of WAT were collected for standardized biochemical, histological, and biophysical evaluations. The inclusion of L-tryptophan in the high-calorie diet led to the inhibition of visceral fat accumulation and reduced levels of total lipids, cholesterol, and triglycerides in the blood serum. Rats in Group III exhibited smaller adipocyte sizes, larger cell nucleus areas, and a decreased relative area of connective tissue in the WAT compared to Group II animals. Tryptophan also mitigated disturbances in WAT bioimpedance among obese rats. These findings suggest that L-tryptophan can attenuate the manifestations of VO and reduce fat accumulation in WAT, thus holding promise for disease prevention.